Nas margens da presença: a questão do logos em Merleau-Ponty - Andrade, André Dias de (2019)
This thesis establish the infrastructure of logos in philosophy of Merleau-Ponty. Firstly we approach de structural aspects of perceptual logic to, utterly, confront this with a general reformulation of sense based on the notion of structure and the development of a new version off phenomenological logos. The research has three fronts that provide a elucidation fr the problems of sense, time and motion. Firstly, we reconstruct the question based on the project of a philosophical rehabilition of perception – called “qualitative turn” – wich has to be conceived as a theory of sense. Secondly, we critically read this fenomenology of percepton and the ideia of “presence” underlying its logos. We show that de descritive and genetical approach of perception, though is based on the disscovery of a eminently positive meaning for the sensorial self-oganisation, it dos not touuch a reconfiguration of logos such as estabslihed by transcendental phenomenology. Finally, we deal with the discovery of a new notion of sense, as “difference”, wich confer autonomy to the logos regarding conscience, besides enabling a new treatment to phenomenality. The broader consequence thiss philosophy is that it renounces to treat logos from a view that corresponds to the “phenomenology of presence”, and só circunscribe it to a “phenomenology of difference” whose constituiton is here desccribed.